Deviation-Correcting Interface for Building-Envelope Renovation - Kepa Iturralde; Ernesto Gambao; Thomas Bock (Buildings, 2023)
In order to reach a Zero-Energy-consuming building stock, it is necessary to insulate and add renewable energy sources on top of existing building envelopes. Off-site prefabricated modules have been used for covering building facades, but manual on-site installation procedures are still more competitive than prefabricated ones. Renovation with prefabricated modules requires high precision in order to obtain airtight and waterproof conditions. For that, an accurate installation of the anchors on top of the facade is crucial. With current techniques, this is a time-consuming operation. One of the attempts to solve the above-mentioned issue was to place the part of the anchor on top of a building facade with high tolerances and to use an interface to correct the deviations. In previous research, this concept, named Matching Kit, was validated, but improvements needed to be made to make it more competitive. In this paper, thanks to novel algorithms and the use of Point Clouds, an improved version is presented. The results show a reduction in working time and an increase in precision. With this research, the interface is closer to being used in the construction industry.